2020
DOI: 10.1177/0276146720935157
|View full text |Cite
|
Sign up to set email alerts
|

Trust-Driven Entrepreneurship for Community Well-Being of Refugees and Their Local Hosts

Abstract: This article explores community well-being (CWB) outcomes of institutional trust (and distrust) through entrepreneurship in the context of a refugee-hosting society in Turkey. Existing studies show the positive relationship between institutional trust and quality of life (QOL) as well as entrepreneurship and QOL in subsistence contexts. This research, however, explores the relationship between institutional (dis)trust and entrepreneurship on a path to CWB with a special emphasis on refugee and local interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…Despite relatively earlier research endeavors in refugee entrepreneurship (Wauters and Lambrecht, 2006;Fong et al, 2007;Wauters and Lambrecht, 2008), the topic has recently regained recognition in the entrepreneurship arena due to the increasing global interest in the refugee crisis. Research highlights the need to assess entrepreneurship not only as a path to deal with refugee-related issues, including integration (Wauters and Lambrecht, 2006), well-being (Baktir and Watson, 2020) and self-reliance (Skran and Easton-Calabria, 2020), but also as a useful tool that contributes economic and social benefits to the hosting societies (Wauters and Lambrecht, 2008;Harb et al, 2019). For instance, Harb et al (2019) challenged the reductionist discourse on refugees as being an economic and social burden and note that, through entrepreneurship, refugees may potentially contribute to local economic development.…”
Section: Refugee Entrepreneurshipmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite relatively earlier research endeavors in refugee entrepreneurship (Wauters and Lambrecht, 2006;Fong et al, 2007;Wauters and Lambrecht, 2008), the topic has recently regained recognition in the entrepreneurship arena due to the increasing global interest in the refugee crisis. Research highlights the need to assess entrepreneurship not only as a path to deal with refugee-related issues, including integration (Wauters and Lambrecht, 2006), well-being (Baktir and Watson, 2020) and self-reliance (Skran and Easton-Calabria, 2020), but also as a useful tool that contributes economic and social benefits to the hosting societies (Wauters and Lambrecht, 2008;Harb et al, 2019). For instance, Harb et al (2019) challenged the reductionist discourse on refugees as being an economic and social burden and note that, through entrepreneurship, refugees may potentially contribute to local economic development.…”
Section: Refugee Entrepreneurshipmentioning
confidence: 99%
“…Yet, despite valuable research endeavors, scholarly discussion on refugee entrepreneurship is still immature (Desai et al, 2021). Specifically, existing theoretical assessments are largely exploratory (Bizri, 2017;Alrawadieh et al, 2019;Harb et al, 2019;Shneikat and Alrawadieh, 2019;Baktir and Watson, 2020;Embiricos, 2020) with little focus on entrepreneurial endeavors of refugees in the tourism and hospitality industry (Shneikat and Alrawadieh, 2019;Alrawadieh et al, 2021). An investigation of refugees in general and refugee entrepreneurship in tourism and hospitality in particular is timely because refugee flows influence the "travelers' experience" of visiting different destinations (Zenker et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The author identified that the topic of entrepreneurial tendencies is the leading topic among Turkish researchers publishing in national scientific journals. A similar tendency can be seen in articles available via Web of Science in the last two years, as many scholars are engaging in measuring entrepreneurial tendencies (Gürel et al, 2021;Özcan et al, 2021;Yalçıntaş et al, 2021), understanding the impact of Syrian refugee entrepreneurs on Turkish economy (Baktır & Watson, 2021;Chang, 2021;Kachkar, 2019) and how women entrepreneurs are changing the entrepreneurship scene in Turkey (Ármane et al, 2021;Bozoğlu Batı & Armutlulu, 2020;Erdoğan, 2020;Kurteğe Sefer, 2020). (Öner & Kunday, 2016) notice that entrepreneurship support started to increase and become more visible since 2006.…”
Section: Literature Reviewmentioning
confidence: 61%
“…PE acts that lack a moral cover and, in turn, public support, risk harm to their political capital—power generated in political networks—useful for negotiating legal deals. REs too need a moral cover to protect their social capital—a social license informally allowing a business to operate (e.g., 2021; Gunningham, Kagan and Thornton 2004)—to be able to negotiate deals. EA activity that the public finds unattractive, such as transactions designed to evade law enforcement, erodes stakeholder perceptions of the RE's trustworthiness and legitimacy (Sale 2019).…”
Section: Hypothesis Developmentmentioning
confidence: 99%